Romance In The Novel Where Angels Fear To Tread By Edward Morgan Foster - Nititham, Nifaraz; Sukmawaty, Fenty; Pertala, Erik Candra (International Journal of Education, Information Technology, and Others, 2025)
This research is entitled Romanticism in the Novel Where Angels Fear to Tread by Edward Morgan Forster and aims to analyze how aspects of romanticism, both in active and passive forms, are reflected through the main characters in the novel. The method used is qualitative-descriptive analysis with a literary studies approach, especially the classical romanticism theory formulated by Lovejoy, Taum, and Faruk, as well as the concept of modern romanticism proposed by Wood. The results show that romanticism in this novel is realized through deep feelings, inner conflict, courage to defy social norms (active romanticism), as well as resignation and suffering due to obstruction of desire (passive romanticism). Lilia Herriton and Caroline Abbott are depicted as active romantics who dare to fight for love and freedom, while Philip Herriton, Harriet, and several other characters reflect passive romantics who are trapped in indecision and social conformity. This research is expected to enrich the treasure of literary studies, especially in understanding the relevance of classical and modern romanticism values in English literature.